Topical Steroid Induced Iatrogenic Cushing Syndrome in Young Adult Age Group: A Case Report - George, Minu Kotheth; James, Apollo; Reddy, Sudhakar; Yasaswini, Bandlamudi; kumar, T R Ashok; Sivakumar, Thangavel (Indian Journal of Pharmacy Practice)
Background: Cushing syndrome is a systemic disorder, occurs as a result of abnormal blood level of cortisol. Prolonged use of topical corticosteroid may cause Cushing syndrome which is very rare and only a few patients have been reported to date in the literatures. Objectives: To evaluate the prompt medical care given for topical corticosteroids induced Iatrogenic caushing syndrome. Results: Clinical symptoms are reduced within one week of treatment with Methotrexate, Prednisone and emollients. Conclusion: Results of the study indicates that the health awareness should be created among general public to avoid the unnecessary drug induced complications.
Keywords: Hypothalamo pituitory-adrenal axis suppression; Iatrogenic Cushing’s syndrome; Psoriasis vulgaris; Topical corticosteroids